Studi implementasi cad/cam pada proses milling cnc terhadap kekasaran permukaan dan tingkat kepresisian aluminium 6061 - Risdiyanto Edy Saputro; Indri Yaningsih; Heru Sukanto (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
This research was conducted to find out the influence of the implementationof CAD/CAM for CNC milling process to the surface roughness andprecision. Specimens were made by using seven types of cutting process.There are face milling, pocket milling, profile milling, slot milling, drilling,thread milling, and surface contouring. The results showed that theimplementation of CAD/CAM with a variation of the cutting processproduces roughness value which is lower than without the implementation ofCAD/CAM. The surface roughness values for each of the cutting processwere face milling process (0.5028 Î¼m; 0.5132 Î¼m), slot milling (0.664 Î¼m;0.6556 Î¼m), profile milling (1.282 Î¼m; 1.3128 Î¼m), pocket milling (1.3852Î¼m; 1.4856 Î¼m) and drilling process (1.9944 Î¼m; 2.1136 Î¼m). The averagevalue of the dimensions from the measurement showed the differencebetween the results of the implementation of CAD/CAM and without theimplementation of CAD/CAM. The percentage difference in the length andwidth were respectively 0.037%; 0.059% for profile milling; 0.039%;0.061% for pocket milling; and 0.151%; 0.317% for drilling. Statistical useof the implementation of CAD/CAM does not significantly affect the value ofthe surface roughness but it has a significant influence on the precision ofthe product with a 95% precision level.